Ledina - Samardžić, Ljubiša (Serbia and Montenegro : Cinema Design Belgrade ; Samardžić, Ljubiša ; Budak, Zoran, 2003)
The film is set in the early autumn of 1995 in the outskirts of Belgrade where a family of musicians just moves in. Dragan, a cellist and a teacher in a music school is Serbian and his wife, a flute player is Croatian. The whole family finds it hard to adapt to the new environment. Nine-year-old son Petar can not make friends with other children, who tease him because he comes from a mixed marriage. The wife is frequently provoked by ethnically related comments and in fact, most of this noisy neighborhood, full of refugees from all over former Yugoslavia, is hostile to the newcomers, especially the crazy chairman of the building Ostoja and a trio of bitter idle middle aged women. In the atmosphere of constant distrust and rampant racism, any situation can inflame brutal responses. A tragic finale is set when Ostoja decides to cultivate a yard in front of the building. Driven to insanity by the local delinquents who constantly ruin his efforts, he loads his gun ready to kill the first intruder. Unfortunately, the victim happens to be little Peter and the marriage finally breaks up.
Keywords: Fiction films